3D-printed fuel-cell bipolar plates for evaluating flow-field performance. Issue 2 (8th June 2020) - Piri, Hossein; Bi, Xiaotao T; Li, Hui; Wang, Haijiang
Abstract: In the last decade, many researchers have focused on developing fuel-cell flow-field designs that homogeneously distribute reactants with an optimum pressure drop. Most of the previous studies are numerical simulations and the few experimental studies conducted have used very simple flow-field geometries due to the limitations of the conventional fabrication techniques. 3D printing is an excellent rapid prototyping method for prototyping bipolar plates (BPPs) to perform experiments on new flow-field designs. The present research investigates the applicability of different 3D-printed BPPs for studying fluid-dynamic behaviour. State-of-the-art flow-field designs are fabricated using PolyJet 3D printing, stereolithographic apparatus (SLA) 3D printing and laser-cutter technologies, and the pressure-drop and velocity profiles are measured for each plate. The results demonstrate that SLA BPPs have great promise in serving as a screening tool in modifying flow-field design with a small feature size. Abstract : Polymer electrolyte membrane (PEM) fuel cells have many advantages over other types of fuel cells. 3-D printing of key components lets designers quickly evaluate new designs, which could reduce the cost, weight, and volume of fuel stacks. Graphical Abstract: